Double-Curie-temperature composite foil and preparation method thereof
By using a dual-Curie temperature composite foil, combined with a magnetic metal matrix and ferrite magnetic particles, the problem of low temperature control accuracy in decentralized electromagnetic heating low-temperature cigarette products is solved, achieving high efficiency and low cost The temperature control effect.
Patent Information
- Application Number
- CN202411762582.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-21
AI Technical Summary
In decentralized electromagnetic heating low-temperature cigarette products, the separation of the heating element and the instrument makes it difficult to measure and control the temperature. The prior art temperature control accuracy is low, the manufacturing process is complex, and the cost is high.
Using a bicurie temperature composite foil, including a magnetic metal matrix and a composite foil made of ferrite magnetic particles and molding agent on one side surface, decentralized electromagnetic heating is achieved through precise bicurie temperature. Accurate temperature control of the product.
It improves the temperature control accuracy of decentralized electromagnetic heating products, reduces manufacturing costs, simplifies process flow, and achieves a smaller total thickness, which facilitates continuous production.
Smart Images

Figure CN119497271A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of heating materials for heating cigarettes, and more specifically, to a double Curie temperature composite foil and a preparation method thereof. Background Art
[0002] In the current low-temperature cigarette products using electromagnetic heating technology, the electromagnetic heating body is placed inside the cigarette in a decentralized structure. That is, the heating body is built into the cigarette cartridge in the shape of a needle, sheet or rod. Since the device is simpler in design and does not require cleaning after smoking, it is deeply loved by consumers.
[0003] However, in this type of structure, since the heating element and the device are separated, and the temperature measurement components cannot be directly added inside the cigarette, the temperature measurement and control of decentralized electromagnetic heating products is relatively difficult. Common technologies generally use a single-layer metal strip or a multi-layer metal sheet to bond, and collect and detect current change points for temperature positioning and control through visible ohmic resistance or discrete compensation of different Curie temperatures. However, the temperature control of a single-layer metal sheet is to control the temperature by causing the change of visible resistance due to the Curie temperature, because the matching error of the material Curie temperature has the disadvantage of low temperature control accuracy; while the multi-layer metal compensation temperature control method, through the temperature positioning of the material at the low Curie temperature point, marks the current difference between the positioning temperature and the required heating temperature, that is, the difference between the two peaks on the current curve, thereby positioning the required temperature current value and controlling the temperature, which can effectively improve the temperature control accuracy. However, due to the need to achieve stable compounding of the two materials under extremely thin conditions in terms of structure, the manufacturing process is relatively complicated, such as bimetallic liquid rolling, tape casting, etc., which is extremely costly and difficult to achieve thickness. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a double Curie temperature composite foil, which can be used as a heating material for decentralized electromagnetic heating of low-temperature cigarette products, with low cost and high efficiency.
[0005] Necessarily, the present invention also provides a method for preparing the above-mentioned double Curie temperature composite foil.
[0006] The technical solution provided by the present invention is as follows: A double Curie temperature composite foil comprises a magnetic metal matrix and a composite foil whose surface on one side is formed by cold rolling of ferrite magnetic particles and a forming agent.
[0007] Wherein, the ferrite magnetic particles are selected from one or both of manganese-zinc ferrite and nickel-zinc ferrite.
[0008] Wherein, the magnetic metal matrix is selected from foils made of iron, cobalt and nickel.
[0009] Wherein, the Curie temperature of the magnetic metal matrix is not less than 350°C.
[0010] Wherein, the raw material thickness of the magnetic metal matrix foil is 0.1-0.3 mm.
[0011] Wherein, the Curie temperature of the ferrite magnetic particles is not higher than 300°C.
[0012] Wherein, the size of the ferrite magnetic particles is 10-100 μm.
[0013] Wherein, the thickness of the double Curie temperature composite foil is 0.05-0.15 mm.
[0014] The molding agent is composed of 95wt%-97wt% ethanol and 3wt%-5wt% phenolic resin, and the molding agent accounts for 40%-60% of the total weight of the ferrite magnetic particles and the molding agent.
[0015] The Curie temperature described in the present invention can be measured by a magnetometer.
[0016] A method for preparing the double Curie temperature composite foil as described above comprises: (1) Cleaning: Pickling the magnetic metal substrate to remove the surface oxide film and contaminants; (2) Ball milling: Place the ferrite magnetic particles into a ball mill, then add high-purity ethanol and perform ball milling to mix the materials; the ball-to-material ratio is 5:1-10:1, the rotation speed is 150-300 rpm, and the ball milling time is not less than 2 hours; (3) Drying: The prepared powder slurry is vacuum dried at a temperature of 70-90°C; (4) mixing glue: mixing the dried mixed powder with a forming agent and homogenizing the mixed powder, wherein the forming agent is composed of 95wt%-97wt% ethanol and 3wt%-5wt% phenolic resin, and the forming agent accounts for 40%-60% of the total weight of the mixed powder and the forming agent; (5) Spray granulation: the slurry mixed with glue is granulated in a spray granulator, with an inlet temperature of 100-120°C, an outlet temperature of 70-85°C, a pressure of 0.05-0.08MPa, a feed rate of 100-200ml / min, and an average particle size of 30-50μm after granulation; (6) coating: the granulated powder is evenly coated on the single-side surface of the foil in step (1) by cold spraying, the spraying gas pressure is 0.6-1.2 bar, the spraying temperature is 100-300° C., and the spraying distance is 10-15 mm; (7) Rolling: The sprayed composite foil is rolled in a cold rolling mill with a rolling ratio of 50% and a rolling temperature of room temperature; (8) Annealing: The rolled composite foil is placed in an annealing furnace for reduction annealing. The annealing atmosphere is H2, the pressure is 0.8-1.0 bar, the annealing temperature is 900-1200°C, and the holding time is 6-12 hours.
[0017] Compared with the prior art, the double Curie temperature composite foil of the present invention comprises a magnetic metal substrate and a composite foil formed by cold rolling of ferrite magnetic particles and a forming agent on one side of the substrate. The composite foil with double Curie temperature is used as a heating material for decentralized electromagnetic heating of low-temperature cigarette products, which facilitates precise control of heating. The present invention has the following advantages: (1) The composite foil has a precise double Curie temperature, which is beneficial to improving the temperature control accuracy of decentralized electromagnetic products; (2) The total thickness of the composite foil is small, which is conducive to the continuous production process from molding to cigarette cartridges; (3) The metal substrate and ferrite particles are semi-metallurgically and semi-mechanically bonded, and the production process is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0021] It should be noted that when an element is referred to as being "fixed on" or "set on" another element, it can be directly on the other element or indirectly set on the other element; when an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0022] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0023] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" and "several" is two or more, unless otherwise clearly and specifically defined.
[0024] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.
[0025] The sources of materials used in the embodiments of the present invention are as follows: Iron metal foil: from commercial sources; 1J50 iron-nickel alloy foil: commercially available; FeCo alloy foil: Co≤50wt%, commercially available; 430L stainless steel foil, commercially available; Phenolic resin: commercially available; The remaining substances were from commercial sources.
[0026] In the embodiment of the present invention, the ball-to-material ratio refers to the mass ratio.
[0027] Example 1 The double Curie temperature composite foil was prepared as follows: (1) Cleaning: Pickle the 0.1 mm thick iron metal foil to remove the surface oxide film and contaminants; (2) Ball milling: 10 μm manganese zinc ferrite particles were placed in a ball milling jar, and then high-purity ethanol was added and ball milled to obtain a powder slurry; the ball-to-material ratio was 5:1, the rotation speed was 150 rpm, and the ball milling time was 2 h; (3) Drying: The prepared powder slurry is vacuum dried at a temperature of 70°C; (4) mixing glue; mixing the dried powder slurry with a molding agent and homogenizing the mixture, wherein the molding agent is composed of 97 wt% of ethanol and 3 wt% of phenolic resin, and the molding agent accounts for 40.00% of the total weight of the mixed powder and the molding agent; (5) Spray granulation: the slurry mixed with glue is granulated in a spray granulator, with an inlet temperature of 100-120°C, an outlet temperature of 70°C, a pressure of 0.05MPa, a feed rate of 100ml / min, and an average particle size of 30μm after granulation; (6) Coating; such as Figure 1 As shown, the granulated particles 200 are uniformly cold-sprayed on a single side surface of the magnetic metal substrate (foil) 300 described in step (1) through a spray nozzle 100 of a spraying machine; the spraying gas pressure is 0.6 bar, the spraying temperature is 100° C., and the spraying distance is 10 mm; (7) Rolling: The sprayed composite foil is rolled in a cold rolling mill 400, with a rolling ratio of 50% and a rolling temperature of room temperature; (8) Annealing: placing the rolled composite foil in an annealing furnace for reduction annealing; the annealing atmosphere is H2, the pressure is 0.8 bar, the annealing temperature is 900°C, and the holding time is 6 hours.
[0028] Example 2 (1) Cleaning: Pickle the 0.3 mm thick 430L stainless steel foil to remove the surface oxide film and contaminants; (2) Ball milling: 100 μm nickel-zinc ferrite particles were placed in a ball milling jar, and then high-purity ethanol was added and ball milled to obtain a powder slurry. The ball-to-material ratio was 10:1, the rotation speed was 300 rpm, and the ball milling time was 12 h. (3) Drying: The prepared slurry is vacuum dried at a temperature of 90°C; (4) mixing glue; mixing the dried mixed powder with a molding agent and homogenizing the mixture, wherein the molding agent is composed of 95wt% and 5wt% phenolic resin, and the molding agent accounts for 60.00% of the total weight of the mixed powder and the molding agent; (5) Spray granulation: the slurry mixed with glue is granulated in a spray granulator with an inlet temperature of 120°C, an outlet temperature of 85°C, a pressure of 0.08 MPa, a feed rate of 200 ml / min, and an average particle size of 50 μm after granulation; (6) Coating; such as Figure 1 As shown, the granulated particles 200 are evenly cold-sprayed onto a single side surface of the magnetic metal substrate (foil) 300 described in step (1) through a spray nozzle 100 of a sprayer; the spraying gas pressure is 1.2 bar, the spraying temperature is 300° C., and the spraying distance is 15 mm.
[0029] (7) Rolling: The sprayed composite foil is rolled in a cold rolling mill 400, with a rolling ratio of 50% and a rolling temperature of room temperature; (8) Annealing: The rolled composite foil is placed in an annealing furnace for reduction annealing. The annealing atmosphere is H2, the pressure is 1.0 bar, the annealing temperature is 1200°C, and the holding time is 12 hours.
[0030] Embodiment 3: (1) Cleaning: Pickling 0.15 mm thick 1J50 iron-nickel alloy foil to remove surface oxide film and contaminants; 2) Ball milling: 50 μm nickel-zinc ferrite particles were placed in a ball milling jar, and then high-purity ethanol was added and ball milled to obtain a powder slurry. The ball-to-material ratio was 7:1, the rotation speed was 200 rpm, and the ball milling time was 10 h. 3) Drying: The prepared powder slurry is vacuum dried at a temperature of 90°C; 4) Adding glue: Mixing the dried mixed powder with a molding agent and homogenizing the mixture, wherein the molding agent is composed of 96wt% and 4wt% phenolic resin, and the molding agent accounts for 55.00% of the total weight of the mixed powder and the molding agent; (5) Spray granulation: The slurry mixed with glue is granulated in a spray granulator with an inlet temperature of 110°C, an outlet temperature of 80°C, a pressure of 0.07 MPa, and a feed rate of 150 ml / min. The average particle size of the particles after granulation is 40 μm. (6) Coating; such as Figure 1 As shown, the granulated particles 200 are evenly cold-sprayed on a single side surface of the magnetic metal substrate (foil) 300 described in step (1) through a spray nozzle 100 of a sprayer; the spraying gas pressure is 1.1 bar, the spraying temperature is 200° C., and the spraying distance is 12 mm; (7) Rolling: The sprayed composite foil is rolled in a cold rolling mill 400, with a rolling ratio of 50% and a rolling temperature of room temperature; (8) Annealing: The rolled composite foil is placed in an annealing furnace for reduction annealing. The annealing atmosphere is H2, the pressure is 1.0 bar, the annealing temperature is 1000°C, and the holding time is 6 hours.
[0031] Embodiment 4: (1) Cleaning: Pickling the 0.2 mm thick FeCo alloy foil to remove the surface oxide film and contaminants; (2) Ball milling: 35 μm nickel-zinc ferrite powder was placed in a ball milling jar, and then high-purity ethanol was added and ball milled to obtain a powder slurry. The ball-to-material ratio was 7:1, the rotation speed was 220 rpm, and the ball milling time was 48 h. (3) Drying: The prepared powder slurry is vacuum dried at a temperature of 90°C; (4) mixing glue; mixing the dried mixed powder with a molding agent and homogenizing the mixture, wherein the molding agent is composed of 96wt% and 4wt% phenolic resin, and the molding agent accounts for 50.00% of the total weight of the mixed powder and the molding agent; (5) Spray granulation: The slurry mixed with glue is granulated in a spray granulator with an inlet temperature of 120°C, an outlet temperature of 80°C, a pressure of 0.06 MPa, and a feed rate of 180 ml / min. The average particle size of the particles after granulation is 40 μm. (6) Coating; such as Figure 1 As shown, the granulated particles 200 are evenly cold-sprayed on a single side surface of the magnetic metal substrate (foil) 300 described in step (1) through a spray nozzle 100 of a sprayer; the spraying gas pressure is 1.0 bar, the spraying temperature is 180° C., and the spraying distance is 10 mm; (7) Rolling: The sprayed composite foil is rolled in a cold rolling mill 400, with a rolling ratio of 50% and a rolling temperature of room temperature; (8) Annealing: The rolled composite foil is placed in an annealing furnace for reduction annealing. The annealing atmosphere is H2, the pressure is 1.0 bar, the annealing temperature is 1050°C, and the holding time is 6 h.
[0032] The foils prepared in Examples 1-4 were subjected to the following tests, and the results are listed in Table 2: Detection of Curie temperature: Thickness detection:
[0033] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A double Curie temperature composite foil, characterized in that: The invention comprises a magnetic metal matrix and a composite foil sheet whose surface on one side is formed by cold rolling of ferrite magnetic particles and a forming agent.
2. The double Curie temperature composite foil according to claim 1, characterized in that: The ferrite magnetic particles are selected from one or both of MnZn ferrite and NiZn ferrite.
3. The double Curie temperature composite foil according to claim 1, characterized in that: The magnetic metal matrix is selected from foils made of iron, cobalt and nickel.
4. The double Curie temperature composite foil according to claim 1, characterized in that: The Curie temperature of the magnetic metal matrix is not less than 350°C.
5. The double Curie temperature composite foil according to claim 1, characterized in that: The raw material thickness of the magnetic metal matrix foil is 0.1-0.3 mm.
6. The double Curie temperature composite foil according to claim 1, characterized in that: The Curie temperature of the ferrite magnetic particles is not higher than 300°C.
7. The double Curie temperature composite foil according to claim 1, characterized in that: The size of the ferrite magnetic particles is 10-100 μm.
8. The double Curie temperature composite foil according to claim 1, characterized in that: The thickness of the double Curie temperature composite foil is 0.05-0.15 mm.
9. The double Curie temperature composite foil according to claim 1, characterized in that: The molding agent is composed of 95wt%-97wt% ethanol and 3wt%-5wt% phenolic resin, and the molding agent accounts for 40%-60% of the total weight of the ferrite magnetic particles and the molding agent.
10. A method for preparing a double Curie temperature composite foil as claimed in any one of claims 1 to 9, characterized in that include: (1) Cleaning: Pickling the magnetic metal substrate to remove the surface oxide film and contaminants; (2) Ball milling: Place the ferrite magnetic particles into a ball mill, then add high-purity ethanol and perform ball milling to mix the materials; the ball-to-material ratio is 5:1-10:1, the rotation speed is 150-300 rpm, and the ball milling time is not less than 2 hours; (3) Drying: The prepared powder slurry is vacuum dried at a temperature of 70-90°C; (4) mixing glue: mixing the dried mixed powder with a forming agent and homogenizing the mixed powder, wherein the forming agent is composed of 95wt%-97wt% ethanol and 3wt%-5wt% phenolic resin, and the forming agent accounts for 40%-60% of the total weight of the mixed powder and the forming agent; (5) Spray granulation: the slurry mixed with glue is granulated in a spray granulator, with an inlet temperature of 100-120°C, an outlet temperature of 70-85°C, a pressure of 0.05-0.08MPa, a feed rate of 100-200ml / min, and an average particle size of 30-50μm after granulation; (6) coating: the granulated powder is evenly coated on the single-side surface of the foil in step (1) by cold spraying, the spraying gas pressure is 0.6-1.2 bar, the spraying temperature is 100-300° C., and the spraying distance is 10-15 mm; (7) Rolling: The sprayed composite foil is rolled in a cold rolling mill with a rolling ratio of 50% and a rolling temperature of room temperature; (8) Annealing: The rolled composite foil is placed in an annealing furnace for reduction annealing. The annealing atmosphere is H2, the pressure is 0.8-1.0 bar, the annealing temperature is 900-1200°C, and the holding time is 6-12 hours.
Citation Information
Cited By
Dual curie temperature composite foil and preparation method therefor
WO2026118425A1